Anticipation and preparation for every delivery room resuscitation. Issue 5 (October 2018) - Sawyer, Taylor; Lee, Henry C.; Aziz, Khalid
Abstract: A majority of babies initiate spontaneous respirations shortly after birth. Up to 10%, however, require resuscitative measures to make the transition from fetus to newborn. Ideally, the need for resuscitation at birth would be predicted before delivery, and a skilled neonatal resuscitation team would be available and ready. This is not always possible. Therefore, neonatal resuscitation teams must be prepared to provide lifesaving resuscitation at every delivery. In this report, we examine risk factors for resuscitation at birth, discuss the importance of communication between obstetric and newborn teams, review key questions to ask before delivery, and investigate antenatal counseling methods. We also investigate ways to prepare for newborn deliveries, including personnel and equipment preparation, and pre-delivery team briefing. Finally, we explore ways in which neonatal resuscitation teams can improve their preparedness through the use of simulation and post-resuscitation debriefing. This report will help neonatal resuscitation teams to anticipate and prepare for every delivery room resuscitation.